ANALISIS INVESTASI TEKNOLOGI INFORMASI STUDI KASUS PT BANK DANAMON INDONESIA TBK - Khairul Anam; Ni Made Estiyanti; I Made Artana (LPPM Universitas Dhyana Pura, 2021)
ABSTRACTPT Bank Danamon Indonesia, is one of the banks affected by the development of information technology and is the bank with the most employees shrinking among ten medium and large scale banks in Indonesia from 2015-2018. Along with the number of employee depreciation that occurred, the company's revenue and net profit actually increased. This research aims to find out the feasibility of IT/SI investments made in PT Bank Danamon Indonesia. The analysis was carried out using Cost Benefit Analysis calculations including Return On Invesment (ROI), Payback Period (PP), Net Present Value (NVP) and Benefit Cost Ratio (BCR). With a Return on Invesment yield of 1.32%, Payback Period of 0.43, Net Present Value of Rp. 18,826,196, and Benefit Cost Ratio of 9.21 which indicates that the investment has a good profitability with a return time of less than one year.Keywords: information technology investment, Cost Benefit Analysis, Return On Invesment, Payback Period, Net Present Value, Benefit Cost Ratio.ABSTRAKPT Bank Danamon Indonesia , merupakan salah satu bank yang terkena dampak dari perkembangan teknologi informasi dan merupakan bank dengan penyusutan jumlah karyawan paling banyak diantara sepuluh bank dengan skala menengah dan besar di Indonesia dari tahun 2015-2018. Bersamaan dengan jumlah penyusutan karyawan yang terjadi, pendapatan dan laba bersih perusahaan justru mengalami kenaikan. Penelitian ini bertujuan untuk mengetahui kelayakan dari investasi TI/SI yang dilakukan pada PT Bank Danamon Indonesia. Analisis dilakukan dengan menggunakan perhitungan Cost Benefit Analysis diantaranya Return On Invesment (ROI), Payback Period (PP), Net Present Value (NVP) dan Benefit Cost Ratio (BCR). Dengan hasil Return on Invesment sebesar 1.32%, Payback Period sebanyak 0.43, Net Present Value sebanyak Rp. 18.826.196 , dan Benefit Cost Ratio sebanyak 9.21 yang menandakan investasi memiliki profitabilitas yang cukup baik dengan waktu pengembalian yang kurang dari satu tahun.Kata kunci: investasi teknologi informasi,Cost Benefit Analysis, Return On Invesment , Payback Period , Net Present Value, Benefit Cost Ratio.